Combining drought and submergence tolerance in rice: marker-assisted breeding and QTL combination effects - Dixit, Shalabh; Singh, Anshuman; Sandhu, Nitika; Bhandari, Aditi; Vikram, Prashant; Kumar, Arvind (Springer, 2017)
TDK1 is a popular rice variety from the Lao PDR. Originally developed for irrigated conditions, this variety suffers a high decline in yield under drought conditions. Studies have identified three quantitative trait loci (QTLs) for grain yield under drought conditions, qDTY 3.1 , qDTY 6.1 , and qDTY 6.2 , that show a high effect in the background of this variety. We report here the pyramiding of these three QTLs with SUB1 that provides 2–3 weeks of tolerance to complete submergence, with the aim to develop drought- and submergence-tolerant near-isogenic lines (NILs) of TDK1. We used a tandem approach that combined marker-assisted backcross breeding with phenotypic selection to develop NILs with high yield under drought stress and non-stress conditions and preferred grain quality. The effect of different QTL combinations on yield and yield-related traits under drought stress and non-stress conditions is also reported. Our results show qDTY 3.1 to be the largest and most consistent QTL affecting yield under drought conditions, followed by qDTY 6.1 and qDTY 6.2 , respectively. QTL class analysis also showed that lines with a combination of qDTY 3.1 and qDTY 6.1 consistently showed a higher tolerance to drought than those in which one of these QTLs was missing. In countries such as Lao PDR, where large areas under rice cultivation suffer vegetative-stage submergence and reproductive-stage drought, these lines could ensure yield stability. These lines can also serve as valuable genetic material to be used for further breeding of high-yielding, drought- and submergence-tolerant varieties in local breeding programs